1984
DOI: 10.1002/1097-0142(1984)54:4<780::aid-cncr2820540433>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Papillary-cystic neoplasm of the pancreas. Report of two cases and review of the literature

Abstract: Two cases of papillary‐cystic neoplasm of the pancreas are reported in women aged 22 and 23 years. The patient in the first case presented with acute abdominal pain and hemoperitoneum. This form of presentation has not been previously reported. This type of pancreatic tumor is very rare, exclusively affecting young women, and has a good prognosis despite its various histologic features, which suggest a malignant appearance. The authors consider this neoplasm as having an acinar origin because in the cells of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Previously reported ultrastructural findings of rough endoplasmic reticulum, possible pre-zymogen granules, neurosecretory type (endosecretory) granules, rudimentary cell junctions [4,11,15,16], and the generally undifferentiated nature of the cells suggest origin from a multipotential ductular stem cell. Structures called ''large zymogen granules" [ 191 are most likely large lipolysosomes.…”
Section: Distinctive Lamellar Bodies Present In Tumor Cells (Arrowmentioning
confidence: 88%
“…Previously reported ultrastructural findings of rough endoplasmic reticulum, possible pre-zymogen granules, neurosecretory type (endosecretory) granules, rudimentary cell junctions [4,11,15,16], and the generally undifferentiated nature of the cells suggest origin from a multipotential ductular stem cell. Structures called ''large zymogen granules" [ 191 are most likely large lipolysosomes.…”
Section: Distinctive Lamellar Bodies Present In Tumor Cells (Arrowmentioning
confidence: 88%
“…Annulate lamellae were often observed in the tumor cells of p~~.12, 18,24,27,32,35 They are organelles, the origin and function of which have not been clarified, but are considered to be markers for immature or poorly differentiated cells due to their frequent appearance in germ cells, parts of embryonal cells, and neoplasm^.^' From these observations, the histologic origin of PCN is considered to be totipotential immature cells such as those that comprise the pancreatic primordium, developing, in budding form, pancreatic exocrine and endocrine glands during the embryonal development of the pancreas. The concept of PCN as an independent tumor may be supported by its unique clinicopathologic features, but the tumor may be regarded as pancreaticoblastoma with delayed onset due to its histogenesis from totipotential immature cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathologic features of SPT have been well described in recent years, its phenotype could not be clearly related to any of the wellcharacterized cells of the pancreas. Some studies indicated an origin from acinar cells [2,18,21,22,23] or endocrine cells [16,43,46], but the results of most other studies have not been compatible with these suggestions [19,28,36]. The immunocytochemical phenotype is characterized by the frequent expression of vimentin, neuron-specific enolase (NSE), and alpha-1-antitrypsin (AAT) [41].…”
Section: Introductionmentioning
confidence: 99%